The relationship between migration background and knowledge and understanding of personal finance of young adults in Germany. (January 2019) - Happ, Roland; Förster, Manuel
Abstract: Financial knowledge and understanding is needed to function well in society; however, young people with a migration background in Germany have been found to perform worse on tests of financial knowledge than those without. Very little investigation has been made into the relationship between financial knowledge and language ability, and ostensibly no in-depth investigation has been made into the connection between frequency of use of the local language and how it correlates to performance on such tests. In this paper we examine the relationship between migration background and knowledge and understanding of personal finance of young adults in Germany. We administered a validated German version of the Council for Economic Education's Test of Financial Literacy to 1037 individuals between the ages of 17 and 25 and controlled not only for migration background but also for frequency of German language use. In line with results of previous studies, we found participants with a migration background generally had less financial knowledge than those with no migration background. More specifically, migrants who spoke predominantly a language other than German at home demonstrated less financial knowledge than those who spoke German at home with their families. Thus, it is not migration background per se, but rather more obscure variables related to migration background that may influence performance on such tests of financial knowledge.